Atypia in pulmonary cytology: A cytomorphometric analysis of the spectrum of changes between benign and malignant. Issue 8 (10th May 2021) - Layfield, Lester J.; Zhang, Tao; Esebua, Magda; Schmidt, Robert L.
Abstract: Background: Cytopathologists reviewing pulmonary specimens are expected to classify samples into clinically useful categories. Clinicians prefer reports to convey a definitively benign or definitively malignant diagnosis. Cytopathologists recognize a spectrum of morphologic features with increasing degrees of atypia between clearly benign and clearly malignant. A variety of terms are used to convey to clinicians how concerned a cytologist is that a malignancy maybe present. These terms include "atypia", "atypical" and "suspicious for malignancy", but have had variable meanings among cytopathologists and clinicians. Categorization schemes have been proffered to include standardization of terminology with many of these systems containing one or more intermediate categories. Methods: An electronic search of the University of Missouri cytology reporting system was made for all bronchial brushings specimens diagnosed using the Papanicolaou Society of Cytopathology System for Reporting Respiratory Cytology (PSCSR) between January 2019 and December 2019. Slides were reviewed to determine adequate cellularity and preparation quality. From those found to be adequately cellular and of good quality, four bronchial brushing specimens from each PSCSR category were randomly selected. For each case a slide was digitized and at least 70 of the most "atypical" cells were analyzed by the Aperio System for nuclear area and nuclear/cytoplasmic ratio. Distribution of measured parameters among categories was analyzed by the Kruskal‐Wallis test. Results: During the study period, only the PSCSR categories "benign", "atypical" and "malignant" were recorded. A significant difference in distribution of nuclear/cytoplasmic ratio was seen between the "benign" and "atypical" categories but not between the "atypical" and "malignant" categories. The "atypical" category appeared to be bi‐modal indicating that it could be divided into two categories, "atypical" and "suspicious for malignancy". Conclusions: The categories "atypical" and "suspicious for malignancy" served to divide the spectrum of cytomorphologic changes between "benign" and "malignant" into clinically useful groups. The use of these categories is supported by cytomorphometric analysis of bronchial brushing specimens.